2005
DOI: 10.1210/jc.2004-1325
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hepatic Cholesteryl Ester Transfer Protein Expression in Obese Humans with the Development of Type 2 Diabetes Mellitus

Abstract: Cholesteryl ester transfer protein (CETP) is a plasma enzyme that can modulate the profile of lipoproteins and is thus considered: 1) a mediator of vascular disease; and 2) a therapeutic target for vascular disease. In the present study, we pursued a better understanding of the effect of type 2 diabetes on the expression of CETP in obese patients. Obesity was accompanied by a 20% elevation in plasma CETP that was eliminated with the development of diabetes. These differences were observed for both men and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…Our data showed that generally serum CETP concentrations were significantly lower in patients than in a healthy control group, although 5.7% of patients had elevated CETP concentrations. This finding is similar to other re- ports [19][20][21] but not to others [5,14,[22][23][24] in which CETP concentration was approximately the same in diabetic subjects and normal controls [5,14,22] or elevated in type 1 or type 2 diabetic patients [23,24] and diabetic cynomolgus monkeys [12] . The discrepancies could be due to differences in assay method, type of diabetes, genetic or ethnic background.…”
Section: Discussionsupporting
confidence: 90%
“…Our data showed that generally serum CETP concentrations were significantly lower in patients than in a healthy control group, although 5.7% of patients had elevated CETP concentrations. This finding is similar to other re- ports [19][20][21] but not to others [5,14,[22][23][24] in which CETP concentration was approximately the same in diabetic subjects and normal controls [5,14,22] or elevated in type 1 or type 2 diabetic patients [23,24] and diabetic cynomolgus monkeys [12] . The discrepancies could be due to differences in assay method, type of diabetes, genetic or ethnic background.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of the diabetic state on plasma CETP concentration appeared to be attributable to an increased level in diabetic female subjects. The effect of obesity on plasma CETP mass may be absent in diabetes (31), and plasma CETP was unrelated to BMI in the currently studied diabetic patients. Therefore, the higher BMI in female compared with male diabetic subjects does not explain their higher plasma CETP concentration.…”
Section: Discussionmentioning
confidence: 72%
“…Plasma glucose, triglycerides (TG), free fatty acids, and total cholesterol were assayed as previously described (28). Urinary nitrogen was estimated from measurements of urea and creatine in 24-h urine collections (25,27), and these samples were also used to estimate 24-h corticosterone release (25).…”
Section: Methodsmentioning
confidence: 99%